Muzyka ocalona, muzyka ocalająca. O Traktacie o łuskaniu fasoli Wiesława Myśliwskiego - Czyżak, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
Article focuses on interpretation of the last novel written by Wiesław Myśliwski Traktat o łuskaniu fasoli. The author presents biography of hero — musician and homo viator. Novel describes his life and its connections with Polish history in XXth century. Above all, it presents a reflections on the role of music in culture after II World War. In his Traktat... Myśliwski performs anti-logocentric turn — music is created as a sphere of art which has power of salvation: it could save human being life from destruction and could stop destruction of rudimental senses formed European culture.